Indigenous African Knowledge and the Challenge of Epistemic Translation - CODESRIA Bulletin Online, No. 6, May 2025 - Zubairu Wai, (CODESRIA Bulletin, 2025)
Keynote Address: African Fellowships for Research in Indigenous and Alternative Knowledges (AFRIAK), Conference organised by CODESRIA, King Fahd Palace Hotel – Dakar, Senegal, 25–27 November 2024 Prologue Allow me to start by recalling an encounter at another CODESRIA meeting in Dakar, in January 2013. In collaboration with Point Sud (Centre for Research on Local Knowledge), based in Bamako, Mali, CODESRIA had co-organised a conference, ‘Africa N‘ko: Debating the Colonial Library’. The conference had brought together some of Africa’s ﬁnest intellectuals to consider the implications of what Congolese philosopher V.Y. Mudimbe designated a ‘colonial library’ on knowledge production and gnostic practices on and about Africa, as well as imagine the continent beyond the epistemic regions, structuring violence and contaminating vectors of this library. Coinciding with the conference was Operation Serval, a French military intervention in Mali ostensibly to oust Al-Qaeda-linked Islamists who had seized control of the north of Mali and were pushing into the centre of the country. Like every other ‘savage war for peace’, Operation Serval was justiﬁed in the name of a higher ethical purpose: namely, to prevent the Malian state from collapse and rescue it from the savagery of Islamists harkening to irrational and premodern beliefs. Among those attending the conference, however, the concerns were especially over the protection of historical and cultural artefacts – speciﬁcally, the manuscripts and knowledge troves of medieval West Africa housed in a library in Timbuktu, central Mali. Indeed, Timbuktu had, under the kings of Mali and Songhai, ﬂourished not only as an important trading post on the trans-Saharan caravan routes but also as a thriving commercial, cultural, and especially, educational centre in medieval West Africa. The Sankoré Mosque/University, for example, attracted many famous scholars from the Islamic world from as far as Andalusia, Egypt and Syria. And this, in addition to a thriving book trade, established the city as a renowned scholarly centre in the medieval and early modern world. Under the rule of Askia Muhammad the Great of Songhai (1493–152ti), for example, the Sankoré University reached its apogee. Its archives are a signiﬁcant historical and cultural monument and remain one of the most important sources for the reconstruction of West African history. And only a fraction of these invaluable documents has been translated and decoded. Obviously, the need to preserve and protect this archive is beyond debate, and in the context of a conference on the colonial library and its implications for knowledge cultivation practices in Africa, the concerns over the protection of the library of Timbuktu, which forms part of the Indigenous African archives, were well founded and justiﬁed. However, there was a lack of care in the way those concerns were expressed. The Malian crisis to which the conference was responding was itself partially a blowback to the savage military intervention and destruction of Libya by the North Atlantic Treaty Organisation (NATO) two years prior. That event, in which France played a central role, has continued to have catastrophic consequences beyond Libya, as we now know: NATO not only bombed Libya, overthrowing its government and destroying its vital infrastructure, but it also helped to destabilise the Sahel region by ﬂooding it with arms that Islamist militants would use to further destabilise Mali and beyond. A decade later, this security crisis is still playing itself out in the Sahelian states that now constitute the Alliance des États du Sahel (Mali, Burkina Faso and Niger), in addition to Chad, Sudan, Nigeria, northern Cameroon and other areas. One would think that a gathering of some of Africa’s brightest minds at a meeting co- organised by the premier pan-African research institution on the continent would be alarmed not only by the destabilising eﬀects of a rising Islamist militarism but also, and more importantly, by the banalisation of Western militarised interventionism on the continent. In the aftermath of NATO’s misadventure in Libya and the catastrophic consequences it was having on Mali and the Sahel region, the expectation that a gathering of these scholars would at the very least adopt a critical stance and place what the French were doing in Mali and elsewhere in that region in a critical frame proved unfounded. The mood at the conference, in part because of concerns about the library of Timbuktu and its invaluable archives, was very fearful and this manifested in support for the French intervention, for which a statement to the eﬀect was being draned to be adopted by the conference. And the language used to justify this position was very similar to the tropes historically used to legitimate colonial interventions: it was framed in terms of a stalwart external agency, the rational European altruistic actor, intervening to overcome the dark and irrational violence of the Islamists. The panic about the imminent destruction of the library of Timbuktu had made it almost impossible for us to see the historical parallels and the dangerous ground on which we were treading. I was shocked beyond belief. Here was what was supposed to be an anticolonial moment or, at the very least, should have been a moment of sober reﬂection, not only on the archives of colonisation but also its historical and contemporary practices. Instead, the event was turning into a spectacle of hegemonic rearticulation reinscribing itself on the conceptualities of the very library it was supposed to be interrogating. And paradoxically it was reproducing and sanctioning the very modalities of practices archived by the library. A statement calling on France and the international community to do everything possible to prevent the library of Timbuktu from destruction was eventually tabled for the conference to adopt. As the sole dissenting voice, I protested against this attempt to sanction the French intervention in the name of protecting the library of Timbuktu, drawing the attention of the conference to the historical parallels and implications and pleading for us to take a more critical stance. My position, which I stated forcefully, emerged from the fear that appealing to France to intervene to help save the library was naive and complicitous at best. It not only legitimated imperialist violence but also concealed or wrote over French complicity in the very violence it was now being asked to respond to. This, I argued, was tantamount to calling on the arsonist to put out the ﬁre they had started in the ﬁrst place. And invoking a higher ethical imperative as the basis of French action, I argued, was serving once again as a mechanism for reinstantiating and reinforcing French neocolonial agendas and imperialistic vocations in the region. In the end, once it had been voiced, my position led to an uproar in the conference hall, igniting a debate that led many to reconsider and express their own uneasiness with lending their names to the statement. I begin with this encounter to underscore the political and contested nature of notions such as ‘Indigenous’ and how the seemingly innocent call to protect it can serve as an alibi for oppressive power and imperialistic vocations. Indeed, the invocation of ‘Indigenous’, or whatever felicitous nomenclature or terminology is used to designate this category – the local, the subaltern, the autochthonous and so forth – is always under threat of appropriation. If not placed in a proper political context and critical frame, it can serve as a mechanism for the reproduction, legitimation and justiﬁcation of imperial and oppressive power relations. As Sylvia Rivera Cusicanqui (2012) warns in another context, this uncritical invocation of the Indigenous can function as an instrument not only for entangling, hence neutralising, radical impulses for self-determination with oppressive power structures, but also for strategic appropriations, co-options, recuperations, neutralisations, silences, erasures, and invisibilisations. In other words, what is hailed as a site or instrument for imagining alternative futures and knowledge systems can become the object of political and intellectual fantasies that through ornamental and symbolic appropriation and co-options theatricalise localised experiences or existences and entrap them in conquering systems. The importance of this observation owes in part to the fact that we now live in an era that has been characterised as a ‘decolonial turn’, in which the invocation of the Indigenous, the local or subaltern, and the retrieval of their knowledge systems, cosmogonies and embodied histories, has become a prominent feature of conversations about epistemic decolonisation (or decoloniality) and the possibility of imagining worlds and knowledges otherwise. This idea, so widespread and prevalent in the discourses of our time, insists that the recuperation of the embodied histories and living knowledge traditions of Indigenous, local, or subalternised experiences is important for rethinking modernity and its cultural and epistemic traditions and conﬁguring alternative knowledges and imagining alternative futures. Yet, the lack of care taken in invoking the Indigenous can not only lead to the kind of slippage referred to above but also risks turning it into an instrument for imperialistic agendas. Indigenous and Alternative Knowledge in Africa As has become fashionable, especially in decolonial and decolonisationist discourses, Indigenous knowledge designates systems of knowledge, practices and belief systems that are said to be endogenous to a particular local place and culture. It involves claims of the existence of an epistemic essence in local knowledge systems and the ways they comprehend the world; it is this constitutive diﬀerence that is said to make them radically diﬀerent from Western knowledge systems. The idea is that every society or culture has knowledge systems that derive from their own speciﬁc local contexts and cultural milieus and that these systems capture the worldview, cognitive patterns and spirit of that culture. Grounded in the embodied histories and practices of autochthonous systems, these knowledges are said to reﬂect the unique cultural values, cosmographic beliefs and linguistic patterns of Indigenous societies. As the vessel for a collective cultural and historical memory, Indigenous knowledge is said to function both as an explanatory system that allows for the formulation of a cultural worldview and as a monument of the traditions of a given community. As a gnostic and epistemic system, it witnesses to, accounts for, and textualises the experiences of a local culture and place and its accounting for the world, while correlating local customs with discursive practices that constitute them as knowledge systems. In this sense, Indigenous knowledge is endogenous and place-based. It emerges from within speciﬁc local cultural milieus as a living archival monument and historical derivation of a community transmitted over a long period of time from one generation to another. Colonial epistemic and representational schemas sought to radically suppress, discard, write over, and devalue these knowledge systems or violently incorporate them into their own conquering epistemes, as well as use them for instrumental purposes for serving colonising agendas. However, Indigenous knowledge systems continue to constitute signiﬁcant ways of coming to terms with human existence. Following the anticolonial struggles in the 1960s and proceeding well into the 19ti0s, and largely in response to the colonial denigration of African cultures and histories, the idea of decolonisation came to be conceived largely in terms of ‘Africanisation’, ‘indigenisation’ or ‘endogenisation’ (Mbembe 2021). In other words, decolonisation was linked inextricably to both the retrieval of African histories and the revival and celebration of the grounded normativity and embodied histories of autochthonous African cultural, cosmographic, and Indigenous systems for the regeneration of African societies. The focus was not only on a critique of colonial knowledge systems and their perverse ideological and representational schemas, as seen for example in colonial anthropological denigrations of African cultures and societies, and their adverse eﬀects. It was also on the recuperation, reconstruction, and celebration of Indigenous African knowledges, which are said to reﬂect the unique cultural, ethnolinguistic, and cosmogonic beliefs and values of African societies. In disciplines such as history, anthropology, theology, philosophy, and literature, African intellectuals proposed strategies for critically challenging colonial discursive and representational denigration of African historicity, humanity, culture, and systems of thought. Moreover, they sought to rethink the disciplines for Africa and propose strategies for the continent’s regeneration from an African situatedness that drew on Indigenous and alternative knowledges. In The Invention of Africa (19titi), a text that can be read as, among other things, a critical evaluation of these Africanisationist and decolonisationist attempts, V.Y. Mudimbe diﬀerentiates between the pre- independence and post- independence generations of African intellectuals. Whereas ‘the preindependence generation of African intellectuals was mostly concerned with political power and strategies for ideological succession’, he writes, the post-independence generation, frustrated with these strategies, became more concerned with ﬁguring out new ways of collectivising and democratising historical reason, Africanising knowledge, reformulating ‘residual questions concerning ideological power and scientiﬁc orthodoxy’ and aﬃrming the African voice in spaces from which it had hitherto been excluded or radically silenced (Mudimbe 19titi: 1ti1). Writes Mudimbe: Since the 1960s, and more visibly since the 1970s and ‘ti0s, a new generation prefers to put forward the notion of epistemological vigilance. This generation seems much more concerned with strategies for mastering intellectual paradigms about “the path to Truth,” with analysing the political dimensions of knowledge, and with procedures for establishing new rules in African Studies. (Mudimbe 19titi: 36) Cameroonian Jesuit priest and philosopher, Engelbert Mveng (19ti3), captured the mood of this period eﬀectively and forcefully: ‘If political sovereignty is necessary, the scientiﬁc sovereignty is perhaps more important in present-day Africa’. And in this preoccupation, he insists, many routes exist in the search for truth: ‘The West agrees with us today that the way to Truth passes by numerous paths, other than Aristotelian Thomistic logic or Hegelian dialectic. But the social and human sciences themselves must be decolonised’ (cited in Mudimbe 19titi: 36). And one of these routes is through African Indigenous knowledge systems and strategies of Africanisation, rethinking the social sciences from an African standpoint, recuperating and reconstructing the African past and centring African cultures. In a now canonical text, Ngũgĩ wa Thiong’o (19ti6) proposed a decolonisationist strategy that proceeded via the reclamation of linguistic sovereignty. Language, Ngũgĩ suggests, is not only a tool of cultural domination but also a tool for liberation, for it is a carrier of culture and thus embodies a people’s identity, history, and worldview. Colonialism functioned simultaneously through the violent imposition of the hegemony of the language of European colonising powers and the radical disruption of the way Indigenous knowledge and values were transmitted, alienating them from their own cultures and forcing them to see themselves through the lens of the coloniser. Therefore, reclaiming the value of Indigenous languages and cultures is an integral part of decolonisation. This reclamation constitutes ‘a liberating perspective’ that would allow Africans to not only express themselves in their Indigenous languages but also ‘see ourselves clearly in relationship to ourselves and to other selves in the universe’ (Ngũgĩ 19ti6: ti7). It thus involves the project of ‘recentring’ African cultures and placing African languages at the centre of projects of African rejuvenation, pedagogical transformation, and imagining relations with the rest of the world. ‘With Africa at the centre of things, not existing as an appendix or a satellite of other’ cultures or societies, Ngũgĩ contends, things will ‘be seen from the African perspective’. Three major tendencies can be identiﬁed in these decolonisationist quests. First, is the process of temporalising Africa as an object of knowledge in a retrospective and prospective parole, caught between an alienated present and an invented glorious past. The second regards the expression of African experiences, cultural systems, and embodied practices as concrete existential realities that can be accounted for by local knowledge systems, and the process of translating them into the language, conceptual categories and epistemic systems of the social and human disciplines. Finally, there is the fundamental question of how Africans can or should relate to and comment on their own beings and conditions without perceiving themselves as being imprisoned in bad faith (Mudimbe 2009). These interventions constituted a reversal of colonial, anthropological or Christian missionary discourses on Africa and represented ‘a break with the ideology inherent in the anthropologist’s techniques of describing African Weltanschauungen’ (Mudimbe 19titi, 1991). However, they also paradoxically employed, functioned and actualised themselves and their credibility within the eﬃciency and the power of the very modern colonial epistemic systems through which Africa was invented and used to negate the pertinence of traditional beliefs and systems of thought, depending as it were, on ‘Western methodological grids [as] a requirement for reading and revealing a deep philosophy through an analysis and an interpretation of linguistic structures or anthropological patterns’ (Mudimbe 19titi: 152). And this was not limited to gnostic attmpts at accessing local knowledge systems but included the projects for African rejuvenation foregrounded by the liberation movements and post-independence governments. ‘Despite the fact that the liberation movements opposed anthropology as a structural factor of colonisation, some pre- and post-independence African policies seem predicated upon the results of applied anthropology’ (Mudimbe 19titi: 1ti4). Indigenous Knowledge and the Decolonial Turn Ngũgĩ’s Decolonising the Mind (19ti6) was one of the last major texts to explicitly think of decolonisation from the perspective of the grounded normativity of African situatedness before the decolonisationist projects were interrupted by the ideological shin that propelled the neoliberal ascendancy. Neoliberalism mounted an assault on the sovereignty of postcolonial African states, and with that the African university, through structural adjustment policies in the 19ti0s. These changes also coincided with the advent of postmodern and poststructuralist modes of inquiry and their scepticisms about the received traditions and categories of modern thought. In this political and ideological climate, the modular nation-state form was attacked and deconstructed, so was any stable conception of politics, identity, culture, knowledge and so forth. Amidst economic crisis and development failures, the unravelling of the postcolonial national state projects and neoliberal restructurings and assaults on the state, these decolonisationist quests were eclipsed or jettisoned while the radical emancipatory politics they championed came to be doubted. In their place emerged Afropessimism, postmodern and poststructuralist modes of inquiry, and speciﬁcally postcolonial theory, which came to champion these critiques in relation to the postcolonial state and the afterlives of colonialism in Africa and the global South more broadly. In recent years, these decolonisationist sentiments have been re-energised by the emergence of what is now known as the ‘decolonial turn’, that is, the current theoretico- political environment in which the politics of decolonisation (redeﬁned as decoloniality) has gained renewed attention. This moment has brought to African consciousness new reasons to propose strategies for rethinking the social and human disciplines for Africa and for African regeneration, based on the embodied histories and grounded normativity of African Indigenous systems. Emerging in the 1990s and consolidating around the Latin American coloniality/modernity research programme, the decolonial turn is said to be anchored on epistemic scepticism about the received Eurocentric accounts of modernity. Speciﬁcally, that coloniality, which is understood as the persistence of colonising structures and logics in postcolonial and contemporary social orders, in global and domestic power hierarchies, knowledge systems, gender norms, conceptions of being and so forth, remains a fundamental problem of modernity; hence the theoretical commitment to decolonisation (redeﬁned as decoloniality) as an unﬁnished project (Quijano 2007; Lugones 200ti; Maldonado-Torres 2011, 2007; Grosfuguel 2007). The group of theorists associated with the decolonial turn had come to believe that despite years of, especially, postcolonial interventions, a new perspective was needed on modernity, its relationship with colonisation, its postcolonial afterlife and how to transcend its structuring matrices (Escobar 2007; Grosfuguel 2007). This belief was partly related to the seeming discomfort and sense of frustration with what had come to be seen as the Eurocentric limitations of the critiques of modernity instantiated by the textual turn. In particular, this unease was caused by what was perceived as the anti- emancipatory limitations of postcolonial theory and its relationship with poststructuralism, as well as with previous attempts at decolonisation. Decolonial theorists claim that previous attempts at decolonisation were limited by their narrow focus on the anticolonial liberation movements and post-independence nation- building projects, and neglect for the epistemic question beyond the ideas of co- contamination with colonial discourse. Walter Mignolo, a leading decolonial theorist, insists that despite the ‘enormous contribution of decolonisation (or independence) …, the limits of all these movements were those of not having found an opening and a freedom of another thinking: that is, of a decolonisation that would carry them … towards a world that would ﬁt many worlds’ (Mignolo 2011a: 50). In a similar vein, Sabelo Ndlovu- Gatsheni (2022), perhaps the leading decolonial theorist in Africa, speaks of ‘truncated African liberation projects’ that resulted in ‘problematic and fragile nation-building processes’ on the continent, hence ‘the myth of decolonisation’ (Ndlovu-Gatsheni 2022: 2).The fact that some of these states were under aaack from the moment independence was proclaimed, as the example of Patrice Lumumba and Congo illustrate, seems to be lost in the fog of attempts at disparaging the signiﬁcance of their contributions. A number of quick points. First, the decolonial turn may be thought of as a re-turn, that is, as an attempt to return to or take up the unﬁnished or interrupted project of historical decolonisation, which is now reformulated mainly in terms of epistemology and relabelled ‘decolonial’. Second, it can be read as a response to what had come to be characterised, rightfully or otherwise, as the anti-emancipatory limitations of the textual turn and, especially, postcolonial theory. Finally, it is primarily epistemic, that is, a quest to delink from the logic of coloniality that they claim is sustained at the epistemic level. As a result, signiﬁcant attention has been focused on the epistemic dimensions of coloniality and its co- imbrication with modernity. There is, decolonial theorists insist, a global epistemic hierarchy that privileges Western subjectivity, knowledge systems, beings and so forth over non-Western ones. More speciﬁcally, the West masks its own local and particularistic viewpoints as detached, ungrounded, superior, and universal, while representing non-Western knowledges and perspectives as particular, subordinate, less valuable and incapable of advancing universal and transcendental consciousness. Decolonial thought, thus, seeks to challenge the dominance of Western geopolitics of knowledge by disarticulating the locus of enunciation from its modern colonial conﬁgurations and resignifying it through a curative, recuperative and restorative practice that grounds the geohistorical locations and biographic inscriptions of localised, Indigenous and subalternised experiences, voices, histories and knowledges (Mignolo 2000, 2011b). Decoloniality – that is, the epistemic condition of delinking from the ‘colonial matrix of power’ – is thus seen as a double preoccupation that must necessarily proceed in two interrelated stages. The ﬁrst involves ‘unveiling the regional foundations of [modernity’s] universal claim to truth’, decentring its locus of enunciations from its modern colonial conﬁgurations. The second, through a geohistoric location and biographic inscription, divests from coloniality and its matrices in order to reimagine modernity beyond its Eurocentric universalistic evocations (Mignolo 2011b: 116). In Africa, despite the existence of a rich history and tradition of decolonisationist thought and praxis that in some sense provides inspiration for the Latin American iteration, it is some of these decolonial ideas and concepts that have been taken up to resurrect and provide the conceptual and theoretical anchor for decolonisationist projects on the continent in recent time. Even scholars such as Sabelo Ndlovu-Gatsheni (2022), who have championed the cause of epistemic decolonisation in Africa, have had to partially mediate their thought through these projects. The result is that historical decolonisation on the continent is conﬂated with contemporary decoloniality without really specifying their diﬀering epistemic, political, and ideological foundations and regions of emergence. Towards a Critique The idea that the embodied histories and living knowledge traditions of Indigenous and subaltern existences and experiences are important for rethinking modernity, its cultural and epistemic traditions and material, political, and sociohistorical conﬁgurations is an important insight for rethinking the discursivity of the modern disciplines and imagining alternative futures. However, my interest is not in the truth value of the prise de parole of this claim. Nor is it in the demand for transforming existing epistemic structures and protocols and imagining the conditions of possibility of the pluralising eﬀects of knowledge cultivation practices that place Indigenous and alternative knowledges at the centre of rethinking modernity and imagining alternative futures. We all agree today that modernity is highly political; that it was constituted through the projection of the European cogito on the world as the locus of the universal; that through a systematic construction of a global political, social, economic and epistemic hierarchy the West placed itself above the non-West, which enabled the West to represent its experience and knowledge as the historical expression of the universal. Therefore, the necessity of provincialising and displacing ‘the Western geopolitics of knowledge’ and recentring alternative knowledge traditions as a means of building alternative futures is not in dispute. My interest is in submitting the claim to close scrutiny to understand its implications for Africa. First is the condition of possibility of situating Indigenous knowledges in decolonisationist practices. For starters, in centring Indigenous knowledge, cultural texts and signifying practices in a restorative praxis, these systems must also be submitted to the external gaze of a conquering episteme that purports to represent them as ‘decolonial’ in order to validate its own praxis. In this way, these projects become captives of the linguistic and epistemic protocols of the modern disciplines and are actualised within the authority and historicity of the very systems they aim to challenge. The discursive ﬁelds of the modern disciplines have themselves been historically implicated in the politics of the production of colonial diﬀerence and its essentialist fetishes. The importance of this point resides precisely in the circularity of the epistemic dependence that it fashions. The emphasis on ‘radical epistemic and ontological otherness’ of the Indigenous thus foregrounds what Scoa Michttlsen and Scoa Cutler Shershow (2007) characterise as ‘epistemological and political acadianism’ (Michttlsen and Shershow 2007: 40), which through a politics of obversion yearns for the purity of the Indigenous subject or position that it valorises. This nostalgia for purity, a yearning for and faith in an ‘unadulterated voice’, recalls Rousseau’s noble savage, imagined as ‘pure’ and undisturbed ‘in the plenitude of its self- presence and self-possession’ (Michttlsen and Shershow 2007: 43). But if the longue durée of colonial modernity has constituted a matrix of power that structures contemporary social orders and power relations, and if in an imperialising period of over ﬁve hundred years everything has become co-entangled and co- contaminated, then how may we ascertain the purity of local cultures or the Indigenous or subaltern voice? How may we know exactly what in local cultures or Indigenous knowledge has been or has not been corrupted by the imprimatur of the colonial matrix of power? Put diﬀerently, how do we know that what is being valorised in local speech, Indigenous cultures, subaltern knowledge and so forth is not, in fact, the inventions, interpolations, or ventriloquisms of the very modern colonial matrix of power that is being contested? Indigeneity does not automatically make a subject inherently radical, neither is Indigenous knowledge automatically emancipatory in and of itself. As a palimpsestic inscription of modern colonialism, it may be tarred with the marks of colonial power and represent the deformities of its authority, identitarian eﬀects and representational violence, which are almost always at risk of being re-implicated in local speech and action. Indigenous knowledge may also reproduce retrograde forms of cultural and identitarian essentialisms in its projects. I would like to recall here Mahmood Mamdani’s (1996) injunction about the political nature of notions such as ‘tradition’, ‘custom’, ‘culture’ or ‘tribe’, which are partially the invention of colonial modernity. The political modernity instituted by late colonialism in Africa, Mamdani tells us, was partly enunciated through the tribalisation of authority. By giving an authoritarian bent to ‘tradition’, colonialism systematically produced and distorted the ‘tribal’ and ‘customary’ as a site or mechanism of modern colonial power. Thus, the customary was and remains tarred by colonial palimpsestic inscriptions. This immediately recalls Eric Hobsbawm and Terence Ranger’s, The Invention of Tradition (1992), as a telling illustration. The issue here is not whether local customs or Indigenous knowledges and traditions exist; neither is it about whether Indigenous groups are capable of speech or action. It is about whether such speech, by virtue of being spoken from a certain location or by a certain body, speciﬁcally a body that has been tarred by colonial palimpsestic violence, can in and of itself be inherently emancipatory. In this regard, I want to refer to the menace of the contaminating violence of what Mudimbe calls the colonial library. As the archival and epistemic conﬁguration of colonial knowledge regimes and representational schemas, it not only contributed to the invention of the very identities and subjectivities being fought over but also constituted a frame that foreclosed the possibility of coming innocently to these identities and subjectivities, and their conditions of existence. In other words, Indigenous subjectivities are not neutral categories but tarred by the palimpsestic violence of colonial power. Almost always already implicated in the production of local histories, cultures, identities, speeches, and subjectivities, the authority of this library also tends to force subaltern, Indigenous, postcolonial subjects seeking to speak with their own voice to imitate or reproduce its preestablished discourse. Similarly, gnostic attempts at apprehending local experiences and retrieving local speeches and histories to refute, resist and transcend the corrupting vectors of the library and its epistemic and representational systems constantly risk reproducing or imitating the contaminating violence of an intransigent library that surreptitiously masks, insinuates, or reimplicates itself. The recuperation of local texts and Indigenous knowledge for overcoming colonialist social formations and advancing a politics of liberation for African rejuvenation thus raises two important questions. The ﬁrst relates to whether one can innocently retrieve local texts or Indigenous knowledges without recourse to an existing archive that threatens gnostic and decolonisationist practices with conceptual contamination. Is it possible (in part because of the contaminating eﬀects of the colonial library) to reveal the past or local cultural and knowledge systems within the context of their own rationality without distorting their chose du texte? Since ‘anthropologists perverted the cultures they had studied’, Mudimbe writes, it would be ‘naïve not to see the catastrophic eﬀects of the anthropologist on the African traditions they have studied and modiﬁed in the name of disciplinary demands’ (Mudimbe 2013: 399). This has continued to haunt the recuperative and gnostic practices that are onen informed by cultural essentialisms or nativist fantasies. The second question relates to whether the danger of epistemological slippage, when gnostic or scholarly attempts at refuting the discourses of the library run the risk of imitating or reproducing them in their frames, can be avoided and under what conditions. In other words, can the structuring violence of the library, which is a menace for attempts at retrieving Indigenous systems, be transcended and under what conditions? The failure to think through these questions or seriously attend to them in a satisfactory way can and is producing simplistic and insuﬃciently conceived conceptions of the condition of postcolonial existence, decolonial transcendence, subaltern resistance, local agency and conditions of converting Indigenous knowledges advanced in the name of a politics of alterity that is completely depoliticised and therefore neither radical nor transformative. The Materiality Question The focus on epistemology has also tended to ignore the material question of historical decolonisation. In fact, the exotic economy of autochthony and the politics of alterity it advances in the name of decoloniality is precisely what neoliberal capitalism needs and targets as key sites of its power and expansionist logics. Recalling Alain Badiou (2003), neoliberalism proliferates through the valorisation of diﬀerence, in the sense that identities that demand recognition through liberal multicultural politics of diversity become key sites for the production and universalisation of the logics of neoliberal capitalist expansion. As this drive articulates itself by targeting sites of diﬀerence, that is, seeking new particulars to which neoliberal universals might be exposed and which might be subsumed under its expansionist logics, so more combinations of territorialised cultural identities and diﬀerences allow neoliberal capitalism to proliferate. It is therefore in the interest of neoliberal capitalism for political struggles about the historical and ongoing structural contradictions of colonial capitalist modernity and its exploitative practices to be framed not in terms of sovereignty or the material, but in cultural, epistemic and identitarian terms for these do not fundamentally challenge the ethos of its logic and practice. And decolonial theory, precisely because it has tended to occlude the materialist impulses of historical decolonisation, focusing instead on the epistemic, cultural, and identitarian, as if those political economy questions and the material conditions that gave rise to them have been exhausted, risks becoming an avenue for, or unwiyng accomplice of, neoliberal traversals and universalising drives. This risk raises the issue of materialism and how it is accounted for in decolonial theory. Let us consider this through the idea of ‘delinking’, which is posited as a strategy for decolonial transcendence. First proposed by Samir Amin (19ti5), delinking was grounded in the materiality of political economy and proposed to advance the Third World Marxist project as a strategy for escaping the structural conditions and exploitative relationship that constrains Southern development in a fundamentally unjust and unequal global capitalist world system that is characterised by exploitation and unequal exchange. However, as appropriated by decolonial theorists, speciﬁcally Walter Mignolo (2007) and Sabelo Ndlovu-Gatsheni (2022) among others, delinking has been uprooted from its political economy groundings, emptied of its materialist content and resigniﬁed as an epistemic strategy. The reason for this strategic appropriation and resigniﬁcation, Mignolo tells us, is that Amin was Marxist. And as part of the Eurocentric archive of modernity, Marxism constrains or prevents the taking over of ‘epistemic power’. Writes Mignolo: Samir Amin’s version [of delinking] is formulated at the level of economic and political (state) delinking. Without an epistemic delinking it is diﬃcult to really delink from the modern notion of Totality. In the case of Amin, he was still caught in the mirage of Marxism and, therefore, of modernity. Thus, his delinking was proposed at the level of the content rather than at the epistemic level that sustain the logic of coloniality. (Mignolo 2007: 502, n. 10) This type of claim also organises Ndlovu-Gatsheni’s (2022: 7–9) reading of Amin. A number of issues arise from the above quote. First, the epistemic, according to Mignolo and Ndlovu-Gatsheni, is the key to unlocking the oppressive structures of colonial modernity and thus may be more important than the material or economic. Second, one gets the impression that Mignolo is claiming to be outside the ‘mirage of modernity’ and that epistemic activism can keep one out of it. This is a vulgar epistemism that submits everything to the epistemic. By epistemism, I refer to the ideological belief in the primacy of epistemology and its construction as the primary factor or moving force of anticolonial liberation, individual autonomy and societal regeneration. And this is held to outstrip and organise all others. Epistemism is a major problem of decolonial thinking. By centring the epistemic and positing a vision of politics grounded on it as the route to anticolonial liberation and transcendence, epistemism both fractures the mutually constituted oppressive structures of colonial modernity and problematically constructs a hierarchy that subsumes the material, political and economic under the epistemic (and with that the cultural, corporeal and identitarian insofar as decolonial epistemic activism proceeds through the body politics and geohistoric location of the decolonial subject) as if there are no material dimensions to the epistemic or cultural. As Fanon warned us a long time ago, anticolonial liberation cannot be reduced to an autochthonous yearning for the revival of a cultural past. In the wake of Negritude and its desire to recuperate the glorious African past and culture, Fanon told us that he was not interested in the revival or exaltation of an African past and its glorious civilisations at the expense of the material present and its future. Speaking in this context, of his lack of desire to direct his energies to reviving an African cultural past at the expense of a suﬀocating present of colonial domination and a possible anticolonial future, he referred speciﬁcally to the people of Indochina and their anticolonial rising: ‘It is not because the Indo- Chinese has discovered a culture of their own that they revolted. Quite simply this was because it became impossible for them to breathe’ (Fanon [1967] 200ti: 201). One can extend the lessons of this injunction to contemporary China and claim that it is not because it has discovered some essential epistemic or cultural truths about its past that it has emerged as a major global power. Rather, it is because marshalling its productive and material forces allowed China to claim political and economic power in the world. Culture is important and is obviously implicated in the Chinese success story, but China is respected and feared primarily because of its economic and political might, not its cultural diﬀerence. By not taking the material seriously as a site for the working of political possibilities, and especially as an instrument of challenging colonial capitalist social formations, political hierarchies and global inequalities underpinned by the logics of coloniality, we miss one of the primary forces that informs and sustains the historical quest for decolonisation and subaltern struggles against exploitative forms of everyday power. Amilcar Cabral’s (1974) warning remains relevant and compelling: ‘the people are not ﬁghting for ideas, for the things in anyone’s head. They are ﬁghting to win material beneﬁts, to live better and in peace, to see their lives go forward, to guarantee the future of their children’ (Cabral 1974: 70). How this future is secured and guaranteed, what strategies are employed or adopted to bring it forth, is what is at stake in this cavalier dismissal of Marxism and its Third World iterations. One may be critical of Amin and raise questions about the condition of possibility of the politics of delinking. One can even question the way he frames it and the strictures within which this politics plays out. However, the idea that his Marxist leanings implicate him in the mirage of modernity and thus rob him of transformational potency, as if Mignolo or Ndlovu-Gatsheni are outside of it, is not valid. As a matter of fact, the same can be said of decolonial theory, which is also captive of the cultural politics of modernity and the linguistic, epistemic and discursive protocols of its knowledge systems. The appropriation of the concept of delinking by Mignolo and other decolonial theorists, and its re- presentation as an epistemological strategy disembedded from its materialist groundings and linkage to the historical struggles of Southern societies as they negotiate the precarity of colonial capitalist exploitation and dependency, as if the material questions have been exhausted or have resolved themselves, also inaugurates its own problems. Since ‘the epistemic locations for delinking come from the emergence of the geo- and body-politics of knowledge’ (Mignolo 2007), the materiality of political economy (as originally framed by Amin) gets replaced by the materiality of the corporeality of subalternised experiences, according to which delinking proceeds via the biographic inscriptions of the subject’s location (i.e., ‘the body politics of knowledge’). The Challenge of Translation Let me now turn to the issue of how Indigenous knowledge is encountered and translated into the conceptual categories and epistemic systems of the modern disciplines, and the challenge this poses for decolonisationist strategies that rely on Indigenous knowledges and local texts for their own praxis. To recuperate Indigenous voices and experiences, local texts and idioms, silenced histories and (or) the practice of everyday life, and use them for decolonial praxis – that is, represent them as the foundation for new knowledge – they must ﬁrst be converted within modern epistemic systems that are themselves vectors of modernity. Such a process, however, is never able to unveil local realities within the contexts of their own rationalities. What it does instead is transmute them into the imprimatur of the intellectual ﬁelds and conceptual categories of the very modern systems being challenged. These eﬀorts to make the experiences intelligible and useful for disciplinary preoccupations are ultimately unable to escape the modernising gaze and discursivity of the modern disciplines and their fetishes. Neither can they escape the power of objectifying discourses that reconstruct them in the language and conceptual systems of disciplines which have themselves been complicit in the historical silences and foreclosures of these groups. Put diﬀerently, beneath the symbolic orders of the recuperative eﬀorts of decolonial practices are the very modern epistemic systems and knowledge practices from which they cannot cut themselves oﬀ completely. The method of accessing and translating Indigenous knowledge into the conceptual categories and epistemic systems of modern disciplines is anthropological; its epistemological locus is the ethnographic foundation and demands of colonial anthropology and its apprehension of local experiences. Constituting its own structural ambit of power, it raises questions about power, the positionality of the theorist, and the credibility of disciplinary procedures and formulations and the discourses they make possible, irrespective of the self-conscious deﬁnition of the theorists or the perspective they adopt or privilege. Such a practice does not and has never been able to resolve the validity problem regarding disciplinary constructions and gnostic practices. Nor does it resolve the question of power and privilege. Ultimately, such a construction, whether based on the interpretation of ethnographic or archival material, or on theoretical speculations and abstractions, or I may add, even the body politics of knowledge à la decolonial theory, will always fall back on its own reconstructed logic that must, through the use of ‘concepts and grids coming from outside the local language and place’, reorganise and reformulate the material for its own purpose (Mudimbe 1991: 102). In the end, ‘a dialogical confrontation’ will take place ‘between the native original place that the concepts exceed and, on the other hand, the scientiﬁc space in which they valorise themselves’. This determines the extent of an appropriative violence and highlights the power relations within which such disciplinary procedures and interpretations are caught. On the one hand, local texts and idioms, Indigenous knowledge systems or subaltern speeches and experiences neither exist by, nor submit to, the logics of disciplinary procedures that they do not know or even care for. They become disciplinary knowledge only through the importation of foreign concepts and the imposition of a disciplinary will that must manage them as objects subjected to the curiosity, gaze, and authority of disciplinary procedures that colonise them within their own schemas while purporting to represent them as new knowledge. But in the attempt to institutionalise an interpretation for political or academic purposes, these local experiences and knowledge systems are removed from the contexts of their own rationality and reorganised, rearranged and re-presented as new knowledge according to the logics of conceptual or analytical systems whose locus of emergence lies not in these local systems themselves but in systems that are the apparatus of the modern epistemes being challenged, and which ultimately distort their chose du texte (Mudimbe 19titi, 1991). Even border gnosis that results from delinking must transcend not only the modern colonial knowledge systems but also the local subalternised knowledges, and resignify them into a new locus of enunciation outside European and Indigenous cognitive patterns. The consequence is the removal of the local experiences, texts, cosmogonies and knowledges from the contexts of their own rationality and their subsumption under the rules of scientiﬁc procedures, disciplinary practices and epistemic and conceptual power of a conquering episteme. To generate or actualise an interpretation, decoloniality must not only mediate the tensions between local cultural realities, or texts that purport to interpret them, and their inscriptions in disciplinary discourses, which have their own rules and rationalities, but must also conceptually bridge and convert those realities/experiences ‘with the “space” of scientiﬁc discourse’ and concepts that come from outside the local place and language (Mudimbe 1991: 101). It is this issue of ‘conceptual bridging’ or translation that constitutes a far greater challenge for decolonial recuperative attempts. This is because disciplinary descriptions or constructions are never simply a reproduction of the dialogic material but an elaborate system of reconstruction dependent on foreign concepts, languages, and procedures. This dialogic tension must be conceptually bridged to make the local texts and experience intelligible for disciplinary procedures and discourses. In this attempt to conceptually bridge, however, a violence is done to the primordial text or speech. This is because disciplinary procedures, which are dependent on their own rationalities and reconstructed logics, entrap local speeches and experiences within their own discourses and purport to represent them as new knowledge or as instruments of decolonial praxis. It is partly for this reason that Mudimbe suggests that we treat every disciplinary construction with suspicion. What these issues highlight for me is the challenge of translating subaltern, Indigenous or local texts, knowledges, and experiences into the conceptual systems and categories of the social disciplines. By translation, I do not refer simply to the practice of rendering a text intelligible from an original language of inscription or enunciation into another but to the politics of conceptual and epistemic bridging. Speciﬁcally, I refer to the practice, and its conditions of possibility, of converting a place, script, idiom, speech, reality, experience, knowledge system and so forth from the contexts of its rationality into the conceptual categories and epistemic systems of the modern disciplines. This politics, which seeks to transmute or transcend an original experience, text, speech or locality and encode it within the conceptual matrices of the modern disciplines, is one of the major ways that Indigenous knowledge is encountered and incorporated in decolonial praxis. It is partly through the politics of translation that decolonisation and decoloniality attempt to transcend coloniality and bring forth decolonial futures. Put diﬀerently, every form of decolonial praxis, beyond mere critique, must attempt to retrieve and translate local experiences and realities into the knowledge capitals of the modern disciplines. But the politics of translation is a parallax. Rather than being a simple process of rendering a text, idiom or experience intelligible from one context to another, it constitutes its own structural ambits of power. This can be seen, for example, in the distance that separates the social scientist and the community that is the object of their gaze, irrespective of whether they originally come from that community or not. Despite protestations to the contrary, there are real power diﬀerentials and hierarchies between the two, in the way that, say, the author of a biography diﬀers from the author of the life that is its object. As Talal Asad (1993) teaches us: a life or experience may produce a script, but ultimately it is the person with a claim to authorial authority who has the power to inscribe it, that is, authorise a particular kind of narrative about that life or experience. Even when both ‘authors’ are the same person, in the case of an autobiography, the basic structuration of this injunction is not impeached. It would still require an elaborate system of temporalising a life, choosing elements, reorganising and rearranging the way it is lived in order to produce a particular narrative or ﬁt it into a particular analytical or narrativising grid. Indeed, no matter how compelling, narratives are never the experiences or realities they are based on or purport to explain: they are always ‘necessarily emplotted in a way in which life is not. Thus, they necessarily distort life whether or not the evidence upon which they are based could be proved correct’ (Trouillot 1995: 6). That every narrative or disciplinary formulation and construction is arbitrary goes without saying. They basically are political and subjective attempts at imposing order on the disorderliness or messiness of phenomena. And they are dependent on the subjective will of the practitioner and on the constraints of the frames of discursivity and disciplinarity within which they operate. In other words, even when practitioners protest otherwise and claim that their work is informed by local experiences, histories, or knowledges, it is they who ultimately get to decide which of those experiences, knowledges, or histories are important for disciplinary purposes. It is they who get to conceptually organise and rearrange those histories and experiences into particular types of narratives in ways that are congruent with their own subjective will and with what is intelligible to the ﬁdelity of ‘scientiﬁc’ practices. In this process, a kind of violence is done to the original text which, as the prehistory or pre-text of the disciplinary exegesis it is used to fashion, is taken out of the context of its own rationality and submitted to the power of a conquering episteme that purports to represent it as new knowledge for whatever purpose. It is for this reason that every disciplinary formulation is conceptually diﬀerent from the material on which it claims to be based; it is always metaphorically designating ‘a new space’ of iteration or new conﬁguration. Put diﬀerently, the material being reconstructed may have come from any source – ﬁeldwork, archival depositories, local cosmographical texts or even speculative abstraction or personal lived experiences – but it always must go through an elaborate process of rearrangement and reorganisation to generate a narrative and thus function as disciplinary knowledge. The point I am making is that translation and conceptual bridging are a ghost in the machine of the modern disciplines and thus a menace to attempts at retrieving local texts and Indigenous knowledge. Every disciplinary formulation, construction, or description is confronted by questions about power and the condition of conversion or conceptual bridging and its practical constraints, irrespective of what ethical or unethical intentions may animate its politics. Put diﬀerently, translating one space, text, knowledge, system, experience, culture, and idiom into another is always fraught. Attempts at converting Indigenous knowledges and local experiences for disciplinary praxis are challenged by questions about power and the condition of possibility of their conversion. First, a translation is not an innocent act but also a will to power or domination, that is, an intellectual consciousness conveying an experience, text, idiom, and so on within speciﬁc disciplinary procedures and through an external relation. In other words, it is the violence that we do onto things: ‘Someone,’ Robert Young (2003) reminds us, ‘is translating something or someone. Someone or something is being translated, being transformed from a subject to an object’ (2003: 140). Second, a translation will always remain a translation. At once a moment and site of rupture, it is always, despite methodological or theoretical precautions, a recreation, an interpretation, an originary reconstruction that can never really reproduce or recreate the pre-text on which it claims to be based. Put diﬀerently, in disciplinary reconstructions, subaltern experiences, local texts, and knowledge systems are always the pre-texts for such constructions. Third, a dialogic tension will always exist between local texts and idioms and the way they are mediated, interpreted, or conceptually converted in disciplinary discourses and preoccupations. Drawing attention to the diﬃculties that fraught gnostic attempts at rethinking Africa through the recuperation and centring of the Indigenous or local knowledge systems, cultural practices and identities is to caution against hasty and often superﬁcial resolutions of the contradictions of colonial modernity and its cultural, identitarian and epistemic eﬀects on African societies as well as against parochial commitments to essentialist visions of politics and postcolonial transcendence. Conclusion Clapperton Mavhunga (2017) has suggested that we take Africa seriously as a site of knowledge traditions and science, technology and innovation, and understand African histories, voices and existence not just as an empirical site for conﬁrming our theories or cannon fodder for theory formation but as a legitimate world-historical region in its own rights. What if we took what Africans know seriously and imagined the world from the location of that knowledge tradition, he asks. What kind of knowledge practices would this require, but more importantly, what type of knowledges would this make possible? Here, Mavhunga is inviting us to take Indigenous knowledges in Africa seriously. Paulin Hountondji (2009) has also suggested the need to ground our pedagogical and scientiﬁc activities in endogenous systems, from our African locations and situatedness: ‘Our scientiﬁc activity’, he writes, ‘is extraverted, i.e. externally oriented, intended to meet the theoretical needs of our Western counterparts and answer the questions they pose. The exclusive use of European languages as a means of scientiﬁc expression reinforces this alienation’ (Hountondji 2009: 12ti). For this reason, suggests Hountondji, the ‘ﬁnal goal’ should be ‘an autonomous, self-reliant process of knowledge production’ deeply rooted in the embodied histories and grounded normativity of African experiences and cultures, a ‘capitalisation that enables us to answer our own questions and meet both the intellectual and the material needs of African societies’ (Hountondji 2009: 12ti). This knowledge system must, however, Hountondji cautions, be ‘grounded in a solid appropriation of the international intellectual legacy and deeply rooted in the African experience’ from an African situatedness (Hountondji 2009: 129). What this means is that we must engage the world and ‘formulate original “problematics,” original sets of problems’ from our African location but must be open to the idea of borrowing and incorporating a multiplicity of inﬂuences, ideas, knowledges, and not be limited by static conceptions and essentialist notions of indigeneity, culture, and knowledges. Thinking Africa through the recuperation and centring of Indigenous or local knowledge systems requires an expansive strategy beyond parochial commitments to essentialist visions of knowledge production. What this means in essence, and to put it analogically in Mudimbean terms, is to ‘invent’ another future; a future that while grounded in African situatedness is not limited by a nativist commitment to primordial cultural essentialisms and static conceptions of identity and culture. Indigenous cultures are never static but dynamic, undergoing constant transformations and being constantly reimagined. While important for this politics of ‘invention’, retrieving Indigenous knowledges should involve what Mudimbe (1994) calls reprendre: to re-apprehend, recapture, resume, take back. It should be a recuperative process of ‘taking up an interrupted tradition, not out of a desire for purity, which would testify only to the imaginations of dead ancestors, but in a way that reﬂects the conditions of today’ (1994: 154). In other words, any attempts at reimagining Africa via Indigenous knowledges, cultures and texts must also, as Mudimbe insists, involve ‘a methodological assessment … beginning, in eﬀect, with an evaluation of the tools, means and projects’ that are being used, as well as inviting a ‘pause, a meditation, a query on the meaning’ of these preoccupations and what they mean and for what purpose (Mudimbe 1994: 154). We have to assess the very project, practice and meaning of recuperation, since much of what passes as radical critique of colonial modernity also functions within its historicity. Let me end by referring, even if brieﬂy, to the example of Fela Kuti, the Nigerian Afrobeat pioneer, and the lessons that his creative will teaches us about the possibility of alternative knowledges and futures in Africa. Fela named his music Afrobeat, though it is a fusion of diverse sounds and inﬂuences: Yoruba percussion, West African highlife, American jazz, funk and soul. While the music is intelligible to jazz and funk lovers, for example, it is not reducible to these genres of music, neither can it be confused with them. Fela proudly called his music Afrobeat (African beat) because he wanted to stress the location and situatedness of its producer, as well as the way he imagined Africa, from where he viewed and made sense of the world. No one can listen to Fela’s music and not understand he is African. Despite the diverse inﬂuences he blended to produce his sound, his African situatedness shines through. By choosing elements from diﬀerent locations to incorporate in his world, he was able to interpret those sounds from his African location, producing timeless music that is as much ‘authentically’ African as say mbalax from Senegambia or rumba from the DRC. Like Fela, African creativity needs not be constrained by autochthonous essentialisms and nativist yearnings for cultural purity; it can blend diverse inﬂuences while remaining distinctly African. With the grounded normativity and embodied experiences of African situatedness as our guide, we can adapt diverse knowledge systems to our unique conditions, integrating them with local traditions, interpreting them from an African perspective. The point I am making is that embracing a more ﬂexible approach to Indigenous knowledge, recognising its dynamic and evolving nature, and integrating it with global knowledge traditions from our African situatedness is more useful than the rigid essentialisms that govern much talk about Indigenous knowledges in Africa.